2014
DOI: 10.1071/hc14195
|View full text |Cite
|
Sign up to set email alerts
|

A patient-centred clinical approach to diabetes care assists long-term reduction in HbA1c

Abstract: INTRODUCTION: Patient-centred care has proven to be cost-effective, with a positive impact on health outcomes. A patient-centred approach is recognised as a desirable component of diabetes care. AIM: The aim of this audit was to determine if the specific patient-centred intervention offered by a clinical service (GPSI Diabetes service) improves diabetes care, as measured by changes in glycosylated haemoglobin (HbA1c). METHODS: The GPSI Diabetes service is a community-based service, run by a general practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…However, diabetes consultations do not often address psychosocial problems due to lack of time or resources or lack of skills and training among doctors 1,6–9 . It is well‐known that a person‐centred approach in diabetes care may improve well‐being and clinical outcomes 1–3,8,10 . Yet, there is a lack of in‐depth research on what makes a diabetes consultation person‐centred from the perspective of adults with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…However, diabetes consultations do not often address psychosocial problems due to lack of time or resources or lack of skills and training among doctors 1,6–9 . It is well‐known that a person‐centred approach in diabetes care may improve well‐being and clinical outcomes 1–3,8,10 . Yet, there is a lack of in‐depth research on what makes a diabetes consultation person‐centred from the perspective of adults with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…mode of action and side effects). Thus, care must be tailored to the specific needs of an individual patient, taking into account his/her preferences, tolerance, needs and values (Inzucchi et al, 2012;Shah et al, 2010;Titchener, 2014). Where in other diseases, diagnosis and initiation of treatment are often the most critical success factors, in diabetes this is only the first step.…”
Section: A Patient-centric Approach To Timely and Appropriate Insulinmentioning
confidence: 98%
“…In order to provide patient-centred care, a physician must adopt the role of an 'educator' and 'partner' rather than being solely a 'decision maker'. The healthcare team must ensure that patients and their family members, as appropriate, acquire sufficient understanding of diabetes and its potential impact on their health, the importance of self-management and available treatment options in order to help them make informed decisions (Titchener, 2014). Educational programmes are particularly useful for teaching patients how to properly initiate, titrate and intensify their treatment according to their prescribed treatments and treatment plan.…”
Section: A Patient-centric Approach To Timely and Appropriate Insulinmentioning
confidence: 98%
“…As a result, the prerequisites for health professionals to give advice on diabetes and to set realistic treatment goals, adapted to the individual patient, may be improved. Moreover, one study has shown that this kind of patient‐centred consultation can also lead to improved outcomes in terms of reduced HbA 1c …”
Section: Introductionmentioning
confidence: 99%